Modified laparoscopic cervicoisthmic cerclage in early pregnancy for refractory cervical incompetence: A case report. Issue 8 (28th May 2019) - Seo, Kohei; Dohi, Satoshi; Ishikawa, Tetsuya; Ichizuka, Kiyotake; Sekizawa, Akihiko; Nagatsuka, Masaaki
Abstract: Modified laparoscopic cerclage was developed as an easy laparoscopic approach during pregnancy, with sutures placed lateral to the uterine vessels. To the best of our knowledge, its successful use in the first trimester has not been reported in Japan. Additionally, there are no published data on chronological assessment of feto‐placental circulation using Doppler. Here, we present the case of a 31‐year‐old Japanese woman (gravida 2, para 1) with refractory cervical incompetence who had a history of preterm birth at 32 weeks of gestation and cervical conization. Modified laparoscopic cervicoisthmic cerclage was performed. Doppler findings showed normal feto‐placental circulation before and after the procedure. Her pregnancy progressed uneventfully with no significant feto‐placental circulation or obstetric complications, and the baby showed normal growth. Elective cesarean section was performed at 37 + 0 weeks' gestation. Modified laparoscopic cervicoisthmic cerclage is suggested as one of the treatment methods for pregnant women with refractory cervical incompetence.